Clinical impact and course of major bleeding with edoxaban versus vitamin K antagonists - Brekelmans, Marjolein P. A.; Bleker, Suzanne M.; Bauersachs, Rupert; Boda, Zoltan; Büller, Harry R.; Choi, Youngsook; Gallus, Alex; Grosso, Michael A.; Middeldorp, Saskia; Oh, Doyeun; Raskob, Gary; Schwocho, Lee; Cohen, Alexander T. (Thrombosis and Haemostasis, 2016)
Edoxaban is a once-daily direct oral anticoagulant (DOAC). The Hokusai-VTE study revealed that, after initial treatment with heparin, edoxaban was non-inferior to and safer than vitamin K antagonists (VKA) in the prevention of recurrent deep-vein thrombosis and pulmonary embolism. This is the first report on the clinical relevance and management of bleeding events with edoxaban. All major bleeding events were classified blindly by three study-independent adjudicators. Predefined criteria were used to classify severity of clinical presentation and, separately, the clinical course and outcome into four categories. Major bleeding occurred in 56 patients treated with edoxaban and 65 patients treated with VKA. The severest categories (3 or 4) of the clinical presentation were assigned to 46 % of the major bleeding episodes in edoxaban recipients versus 58 % of the major bleeds in VKA recipients (odds ratio [OR] 0.62, 95 % confidence interval [CI] 0.30–1.27, p = 0.19). Clinical course was classified as severe (category 3 or 4) in 23 % of the edoxaban and 29 % of the VKA associated bleeds (OR 0.73, 95 % CI 0.32–1.66, p = 0.46). In conclusion, edoxaban associated major bleeding events have a comparable clinical presentation and course to major bleeds with VKA in patients treated for venous thromboembolism in the Hokusai-VTE study. These results may assure physicians that it is safe to prescribe this medication. If a major bleeding during edoxaban treatment occurs, its clinical presentation and clinical course are not worse than in VKA-treated patients.
Keywords: Anticoagulants; coumarins; edoxaban; venous thromboembolism; haemorrhage